Low-power-consumption ultraviolet photodetector based on p-NiO/SiO2/n-ZnO - Vincent Teng (Optics and Laser Technology, 2023)
Ultraviolet (UV) photodetector has found extensive applications, ranging from optical communication to ozone sensing. Wide bandgap metal oxide heterostructures have gained significant interest in the development of UV photodetectors due to their excellent electronic and optical properties, as well as ease of fabrication. However, there are surface and interface issues at these heterostructures that have detrimental effects on device performance. In this work, UV photodetector consisting of p-NiO/SiO2/n-ZnO heterostructure was prepared by RF magnetron sputtering method. The device exhibited remarkable performances, such as having a rectification ratio of 57, responsivity (R) of 5.77 AW-1, external quantum efficiency (EQE) of 1.96×103 % and rise time of 0.048 s at a low power consumption of -0.1 V under 365 nm UV irradiation. This work demonstrated a method for low-cost fabrication of photodetectors with rectification behavior and at low power consumption.